Property prices and regional labor markets in Poland - Drachal, Krzysztof (The European Journal of Applied Economics, 2014)
The purpose of this research is the construction and analysis of a macroeconomic model of property prices in Poland covering the period between 2006 and 2013. The model is based on a supply-demand approach. Property prices have been found to be significantly affected by wages (positive correlation), unemployment rate (negative correlation), construction costs (positive correlation) and size of population (positive correlation). The panel data were collected from the biggest cities in voivodeships (Polish administrative regions). Both models with fixed and random effects were analyzed. Some similarities with a developed (UK) market have been found as well.
Keywords: property market; house prices; regional labor market; unemployment